2017
DOI: 10.4103/2249-4863.222014
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting antiretroviral treatment adherence among people living with human immunodeficiency virus/acquired immunodeficiency syndrome: A prospective study

Abstract: Context:Antiretroviral adherence is the second strongest predictor of progression to acquired immunodeficiency syndrome (AIDS) and death, after CD4 count. Adherence to antiretroviral therapy (ART) has been strongly correlated with human immunodeficiency virus (HIV) viral suppression, reduced rates of resistance, an increase in survival, and improved quality of life.Aims:To determine the adherence rates and factors affecting adherence to ART among people living with HIV/AIDS (PLWHA).Settings and Design:A Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“… 6 Moreover, life-long treatment strongly impairs the adherence, drastically promoting the selection of variants of the virus resistant to current therapies. 7 This resistance phenomenon represents the major clinical challenge in the fight against AIDS. Therefore, new anti-HIV agents are still urgently needed, in particular, inhibitors acting against novel viral targets that can contribute overcoming the resistance issue.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Moreover, life-long treatment strongly impairs the adherence, drastically promoting the selection of variants of the virus resistant to current therapies. 7 This resistance phenomenon represents the major clinical challenge in the fight against AIDS. Therefore, new anti-HIV agents are still urgently needed, in particular, inhibitors acting against novel viral targets that can contribute overcoming the resistance issue.…”
Section: Introductionmentioning
confidence: 99%
“…Poor ART adherence was reported among underprivileged communities where socioeconomic inequalities heighten the risk (Young et al, 2014) and lower quality of life is prevalent (Liping et al, 2015;Hansana et al, 2013), negatively impacting the HIV program (Wang et al, 2011). For PLWHA, factors related to gender dimensions, socioeconomic factors such as education status, income, asset possession and food security have been associated with non-adherence to ART (Basti et al, 2017;Abera et al, 2015;Alagaw et al, 2013). For example, in South Africa (Eyassu, Mothiba & Mbambo-Kekana, 2016), Cameroon (Fonsah et al, 2017) and northern Tanzania (Samuel Edward et al, 2018), gender, income and level of education were reported as the determinants of ART adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Factores relacionados al no cumplimiento de las recomendaciones de la guía de práctica clínica en una IPS especializada en el manejo de VIH/SIDA entre variables clínicas y el cumplimiento o la adherencia, donde 96.8% de los pacientes tuvieron una adherencia optima (>95%), con el recuento de LT-CD4 (p= 0.05) y el efecto de educación a los pacientes por parte de los programas sobre la importancia del cumplimiento y la adherencia a las recomendaciones (p= 0.04). Mientras que las principales variables relacionadas al no cumplimiento fueron alteraciones en la salud mental (p= 0.001), esto podría explicar que ante enfermedades mentales graves que requieren acompañante o cuidador, la asistencia de estos podrían favorecer la adherencia o el cumplimiento a las recomendaciones de la guía de práctica clínica (21)(22)(23). La imposibilidad de este estudio para encontrar factores clínicos relacionados al cumplimiento y la adherencia podría ser explicado por el tamaño de la muestra o que en esta población las variables administrativas tengan mayor fuerza de asociación que las clínicas, sin embargo, dichas variables administrativas no estuvieron disponibles en las fuentes de información consultadas.…”
Section: Discussionunclassified